Not Inconclusive, But Not Quite Conclusive: The Wish to Impose a Literary Theory Upon a Film and Thereby Dissuade It From Its Inferiority Complex (KULT_online, 2013)
In her thesis Claudia Pinkas analyses the unstable, ambiguous worlds of fantastic films and the process of their narrative presentation. Theoretical starting point is Todorov's theory of the fantastic, which is utilized for the film. Pinkas' goal is nothing less than the draft of a fantastic film narratology on the plains of histoire and discours. The goal is achieved with superior ease, and minor blunders are insignificant.